The Correlation Between the Duration of Diabetes Exercise Series 5 and Blood Sugar Levels Among Members of the Indonesian Diabetes Association (PERSADIA) at Mayapada Hospital Bogor - Pitdayani; Desvoita, Eva; Herawati, Lusi; Aryanti, Erna; Syahwa, Azmi Sulintya; Buka, Sisilia Prima Yanuaria (Indonesian Scientific Publication, 2024)
Diabetes Mellitus (DM) is a metabolic condition characterized by elevated blood glucose levels (hyperglycemia), caused by insufficient insulin secretion, impaired insulin activity, or both. One of the management strategies for Diabetes Mellitus is physical exercise. Diabetes exercise is a low-impact aerobic workout recommended by PERSADIA. The fifth series of diabetes exercise, with a duration of 40-60 minutes, is beneficial in converting glucose into energy, thus slowing the progression of diabetes. This study aims to determine the relationship between the duration of the fifth series of diabetes exercise and blood sugar levels in members of PERSADIA at Mayapada Hospital Bogor. The study uses a quantitative descriptive design with a quasi-experimental approach through a one-group pre-posttest design. The research subjects were members of PERSADIA who participated in diabetes exercise, with a total sample of 30 respondents. The results showed that almost all members of PERSADIA at Mayapada Hospital Bogor experienced a reduction in random blood sugar levels (93.3%) after performing diabetes exercise according to the standard operating procedure (40-60 minutes), while 2 members (6.7%) who did not follow the SOP and exercised for less than 40 minutes experienced an increase in blood sugar levels. Statistical analysis using the chi-square test showed a p-value of 0.000, indicating a significant relationship between the duration of the fifth series of diabetes exercise and blood sugar levels in PERSADIA members at Mayapada Hospital Bogor. Conclusion: Diabetes exercise can play a role in regulating blood glucose levels if conducted according to the principles of diabetes exercise, which include meeting the standards of frequency, intensity, duration, and type of exercise.